Pattern of macrophage activation in yersinia-resistant and yersinia-susceptible strains of mice - Tumitan, Ana Rita Paladino [UNESP]; Monnazzi, Luis Gustavo Silva [UNESP]; Ghiraldi, Fabrício Rodrigues [UNESP]; Cilli, Eduardo Maffud [UNESP]; De Medeiros, Beatriz Maria Machado [UNESP] (Wiley, 2007)
Th1 cells, in cooperation with activated macrophages, are required to overcome Yersinia enterocolitica infection in mice. The pathway macrophages utilize to metabolize arginine can alter the outcome of inflammation in different ways. The objective of this study was to verify the pattern of macrophages activation in Y. enterocolitica infection of BALB/c (Yersinia-susceptible) and C57BL/6 (Yersinia-resistant) mice. Both strains of mice were infected with Y. enterocolitica O:8 WA 2707. Peritoneal macrophages and spleen cells were obtained on the 1st, 3rd and 5th day post-infection. The iNOS and the arginase activities were assayed in supernatants of macrophage cultures, by measuring their NO/citrulline and ornithine products, respectively. TGFβ-1 production was also assayed. The Th1 and Th2 responses were evaluated in supernatants of lymphocyte cultures, by IFN-γ and IL-4 production. Our results showed that in the early phase of Y. enterocolitica infection (1st and 3rd day), the macrophages from C57BL/6 mice produced higher levels of NO/citrulline and lower levels of ornithine than macrophages from BALB/c mice. The infection with Y. enterocolitica leads to an increase in the TGF-β1 and IL-4 production by BALB/c mice and to an increase in the IFN-γ levels produced by C57BL/6 mice. These results suggest that Y. enterocolitica infection leads to the modulation of M1 macrophages in C57Bl/6 mice, and M2 macrophages in BALB/c mice. The predominant macrophage population (M1 or M2) at the 1st and 3rd day of infection thus seems to be important in determining Y. enterocolitica susceptibility or resistance.
Keywords: Arginase; Inducible nitric oxide synthase (iNOS); Macrophages; Yersinia enterocolitica; arginase; citrulline; gamma interferon; inducible nitric oxide synthase; interleukin 4; nitric oxide; ornithine; transforming growth factor beta1; amino acid analysis; animal cell; animal experiment; animal model; bacterial strain; Bagg albino mouse; cell culture; controlled study; cytokine production; enzyme activity; enzyme assay; female; infection resistance; infection sensitivity; lymphocyte culture; macrophage activation; mouse; nonhuman; peritoneum macrophage; spleen cell; supernatant; Th1 cell; Th2 cell; yersiniosis; Animals; Citrulline; Female; Macrophage Activation; Macrophages, Peritoneal; Mice; Mice, Inbred BALB C; Mice, Inbred C57BL; Nitric Oxide; Nitric Oxide Synthase Type II; Ornithine; Yersinia Infections; Mus; Yersinia